2018
DOI: 10.1186/s12889-018-6239-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health-related quality of life (HRQoL) among healthy, obese and chronically ill Iranian children

Abstract: BackgroundHealth-related quality of life (HRQoL) has frequently been compared between both healthy and obese children and healthy and chronically ill children; however, there is glaring lack of evidence regarding comparison of HRQoL in obese children with their counterparts with chronic diseases. Therefore, this study aimed to compare HRQoL among healthy, obese and chronically ill children.MethodsThis cross sectional study was conducted among 802 children (8–12 years) who were recruited via convenience samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
1
11
0
7
Order By: Relevance
“…La Organización Mundial de la Salud dene la calidad de vida relacionada con la salud (CVRS) como "las metas, expectativas, estándares o preocupaciones de un niño sobre su salud en general y los dominios relacionados con la salud" (16,17). Este concepto es multidimensional e incluye la función física, social y emocional del niño y su familia, y se trastoca en la mayoría de los niños con enfermedades crónicas, especialmente en aquellos con nivel socioeconómico bajo (18,19,20,21).…”
Section: Introductionunclassified
“…La Organización Mundial de la Salud dene la calidad de vida relacionada con la salud (CVRS) como "las metas, expectativas, estándares o preocupaciones de un niño sobre su salud en general y los dominios relacionados con la salud" (16,17). Este concepto es multidimensional e incluye la función física, social y emocional del niño y su familia, y se trastoca en la mayoría de los niños con enfermedades crónicas, especialmente en aquellos con nivel socioeconómico bajo (18,19,20,21).…”
Section: Introductionunclassified
“…Data available on the relationship between weight status and HRQoL in children is controversial. Several studies showed negative associations between children's weight status and HRQoL [9,10], as demonstrated by the Tsiros et al systematic review conducted on 22 studies, revealing an inverse linear relationship between children's BMI and HRQoL for both pediatric self-reports and parent proxy-reports [50]. Further evidence indicates Iranian children with higher BMI are more likely to report poorer HRQoL [13].…”
Section: Discussionmentioning
confidence: 91%
“…The association between children weight status and HRQoL is controversial. While some studies emphasize the negative impact of childhood obesity on HRQoL [9,10], others have not shown a signi cant relationship between them [11,12]. Similar studies from Iran indicate lower HRQol scores in obese children, compared to their over-or normal-weight counterparts [13,14] which can be observed in a gender-speci c pattern [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the previously cited Iranian study, similar observation can be deduced regarding emotional functioning where boys (mean score=77.0) had lower scores compared to girls (81.5), although they achieved higher physical (90.5 versus 88.0) and social (90.5 versus 87.1) functioning scores, respectively; however, authors did not analyze the statistical significance of this fluctuation being not the scope of their study. 27 Other authors of an Iranian study reported significant gender effect on the QOL among children afflicted with epilepsy, which may denote adjacent sociocultural factors inducing discrepancy between girls and boys. 34 More remarkably, older and medium ages were crucial, especially for boys where behavior and psychological health was relatively disturbed associating impact on parents and family functioning.…”
mentioning
confidence: 97%
“…By focusing on healthy group, comparison with our study reveal fairly comparable findings regarding physical functioning and social functioning, where scores ranged between 80-95 out of 100. 27 Another study by Pinhas-Hamiel investigated the association of obesity with QoL by comparing apparently healthy normal weight versus obese children by means of the PedsQLTM 4.0, using both child-and parent-reported versions. Normal weight children showed >80 mean scores in physical, social and school functioning, whereas emotional functioning showed mean score of 74.1 and 73.2 in child-and parent-reported assessments; 28 which is fairly comparable to findings from our study.…”
mentioning
confidence: 99%